Policy Actors as Determining Factors of Sustainability Village Fund Management in Indonesia - Jamaluddin, Yanhar (Journal of Ecohumanism, 2024)
This study was to identify the roles of policy actors as determining factors for the sustainability of Village Fund management in Indonesia. This policy was realized through a Village Fund allocation program for each Village sourced from the State Revenue and Expenditure Budget (APBN) which was regulated in Government Regulation Number 60 of 2014. Since this policy was implemented from the 2015 to 2022 budget year, the management of Village Funds had not been on target. Descriptive method used in the discussion. Data analysis used a qualitative approach, and the analysis instruments focused on policy actors/institutions. The findings was that the management of Village Fund Policy involved internal bureaucratic actors (official policymakers). The Village Government was the actor/institution that benefitted the process and the Regency Government is the actor/institution that suffered the loss. Thus, the sustainability of Village Fund management policies was determined by political factors, namely the insight and political interests of future government policy makers; and policy actor commitment the factors. This article recommended that to ensure the sustainability of the Village Fund policy, it was necessary to unite the vision and commitment of actors, both policy makers and policy implementers, to synergize Village development programs based on the Regional RPJM.